Facial Emotion Recognition in Schizophrenia - Gao, Zhiyun; Zhao, Wentao; Liu, Sha; Liu, Zhifen; Yang, Chengxiang; Xu, Yong (Frontiers in Psychiatry, 2021)
Defects in facial emotion recognition are one of the most common cognitive impairments, seriously affecting the patients' social functioning, and have been extensively studied in various psychiatric disorders, especially in schizophrenia. However, there is still a lack of conclusive evidence about the factors associated with schizophrenia and the impairment at each stage of the process, posing a challenge to the clinical management of patients. Based on this, we summarize the facial emotion cognition among patients with schizophrenia, introduce the internationally recognized Bruce-Young face recognition model, and review the behavioral and ERP related studies on the recognition of emotions at each stage of the face recognition process, including the future direction of clinical research, in order to continue to explore the processing mechanisms of patients and provide new ideas for interventions.